Philip Roth's Rude Truth : The Art of Immaturity - Posnock, Ross (Book collections on Project MUSE., 2008)
Has anyone ever worked harder and longer at being immature than Philip Roth? The novelist himself pointed out the paradox, saying that after establishing a reputation for maturity with two earnest novels, he "worked hard and long and diligently" to be frivolous--an effort that resulted in the notoriously immature Portnoy's Complaint (1969). Three-and-a-half decades and more than twenty books later, Roth is still at his serious "pursuit of the unserious." But his art of immaturity has itself matured, developing surprising links with two traditions of immaturity--an American one that includes Em